Propargylsilanes as Reagents for Synergistic Gold(I)‐Catalyzed Propargylation of Carbonyl Compounds: Isolation and Characterization of σ‐Gold(I) Allenyl Intermediates. (13th June 2019) - Fernández, Sergio; González, Jairo; Santamaría, Javier; Ballesteros, Alfredo
Abstract: Reported herein is the isolation and characterization, for the first time, of a σ‐gold allenyl complex as an intermediate in gold catalysis. This intermediate was captured during the study of a novel gold(I)‐catalyzed propargylation of carbonyl compounds with propargylsilanes. Notably, the gold‐catalyzed propargylation reaction, which proceeds with aldehydes and ketones, can be driven to the formation of either homopropargyl silyl ethers or the in situ synthesis of corresponding 2‐silyl‐4, 5‐dihydrofurans. Abstract : Gold erschließt zwei Wege : Ein σ‐Gold‐Allenyl‐Komplex wurde isoliert und als Zwischenstufe einer neuartigen goldkatalysierten Propargylierung charakterisiert. Propargylsilane wirken als effektive Reagenzien für die Propargylierung von Carbonylverbindungen. Die Reaktion kann hin zur Bildung von Homopropargylsilylethern oder zur In‐situ‐Synthese von 2‐Silyl‐4, 5‐dihydrofuranen gelenkt werden.